A37 EXPLORING THE PROTEOMICS DIFFERENCES IN CROHN'S DISEASE PATIENTS. (4th March 2021) - Nogueira de Almeida, L; Mainoli, B; Filyk, A K; Hirota, S A; Lu, C; Dufour, A
Abstract: Background: Canada has the highest prevalence rate of Crohn's disease (CD) in North America. In Alberta, the yearly cost of anti-inflammatory drugs can be more than 25, 000 per person; however, half of the patients do not respond to medication. CD is characterized by lesions in the small intestine due to inflammation, promoting diarrhea and abdominal pain. Prolonged chronic inflammation results in fibrotic strictures that are resistant to anti-inflammatory therapies and promote narrowing of the luminal space that ultimately require surgery. Currently, there is no biomarker to distinguish between the inflammatory or stricturing phenotype. Aims: AIM 1: Profile serum samples from CD patients using a label-free shotgun-proteomics. AIM 2: Identify signatures and biomarkers that distinguish inflammatory and fibrotic strictures using a bioinformatics approach. Methods: Serum samples from 15 CD patients with strictures and 15 CD patients without strictures (inflammatory phenotype), as diagnosed by ultrasound imaging, were analyzed by a standard shotgun-proteomics approach. Briefly, 200 µg of serum proteins were processed in a label-free protocol in combination with the filter-aided sample preparation (FASP) method. Liquid chromatography-tandem mass spectrometry was performed on an Orbitrap Fusion Lumos. Protein identification was accomplished by MaxQuant at a 1% false-discovery rate. Statistical significance was determined by the MSstats package, in the R software. To identify the biological significance of disturbed pathways, it was characterized by the protein-protein interactions and pathway enrichment analysis using String-DB and Metascape. Results: It was identified a statistically significant protein panel between the two phenotypes. Proteins identified in the strictured group include JAK1 (Tyrosine-protein kinase), CD5 antigen-like protein (regulates inflammatory gene expression in Th17 cells), and neogenin (cell adhesion). Of the inflammatory patients, there was a significant elevation of PFK/FBPase 2 (synthesis and degradation of fructose 2, 6-bisphosphate), vinculin (cell-matrix adhesion) and MMP-16/MT3-MMP (matrix metalloproteinase). Conclusions: The identification of a distinct signature between both phenotypes provide important biological information about the disease progression and are a good sign that a biomarker discovery platform will be capable to differentiate between inflammatory and fibrostenotic strictures from serum samples of CD patients. Funding Agencies: CAG, CIHRNSERC